Measuring the income-distance tradeoff for rural-urban migrants in China - Junfu Zhang; Zhong Zhao (Institute for the Study of Labor (IZA), 2013)
Rural-urban migrants in China appear to prefer nearby destination cities. To gain a better understanding of this phenomenon, we build a simple model in which migrants from rural areas choose among potential destination cities to maximize utility. The distance between a migrant's home village and destination city is explicitly included in the utility function. Using recent survey data, we first estimate an individual's expected income in each potential destination city using a semi-parametric method, controlling for potential self-selection biases. We then estimate the indirect utility function for rural- urban migrants in China based on their migration destination choices. Our baseline estimates suggest that to induce a migrant to move 10 percent further away from home, the income of this migrant has to increase by 15 percent. This elasticity varies very little with migration distance; it is slightly higher for female than male migrants; it is not affected by the migrant's age, education, or marital status. We explore possible explanations of these results and discuss their policy implications.
Keywords: O15; R12; R23; 330; income-distance tradeoff; rural-urban migration; hukou system; China